GENERATION OF ELECTRICITY USING WATER PIPELINE (International Journal of Engineering Sciences & Management Research, 2017)
There is lot of kinetic energy flowing through domestic water pipeline; this energy can be used in generation of electricity. The turbine can be fitted inside the pipelines by coupling it with generator. Due to the kinetic energy of water the turbine rotates and electricity is generated by the generator. The energy generated by this process is totally pollution free, and it has no hazards to the environment. It also does not affect the flow of water because of gravitational energy. It does not require fuel and it is totally ecofriendly. Abundant energy can be obtained by this process.